Genetic diversity and structuring across the range of a widely distributed ladybird: focus on rear‐edge populations phenotypically divergent. Issue 15 (13th July 2016) - Lecompte, Émilie; Bouanani, Mohand‐Ameziane; Magro, Alexandra; Crouau‐Roy, Brigitte
Abstract: Population genetics and phenotypic structures are often predicted to vary along the geographic range of a species. This phenomenon would be accentuated for species with large range areas, with discontinuities and marginal populations. We herein compare the genetic patterns of central populations of Coccinella septempunctata L. with those of two phenotypically differentiated populations considered as rear‐edge populations and subspecies based on phenotype (Algeria and Japan). According to the central‐marginal model and expected characteristics of rear‐edge populations, we hypothesize that these rear‐edge populations have (1) a reduced genetic diversity, resulting from their relative isolation over long periods of time, (2) a higher population genetic differentiation, explained by low contemporary gene flow levels, and (3) a relationship between genetic diversity characteristics and phenotypes, due to historical isolation and/or local adaptation. Based on genotyping of 28 populations for 18 microsatellite markers, several levels of regional genetic diversity and differentiation are observed between and within populations, according to their localization: low within‐population genetic diversity and higher genetic differentiation of rear‐edge populations. The genetic structuring clearly dissociates the Algerian and Eastern Asia populations from the others. Geographical patterns of genetic diversity and differentiation support the hypothesis of the central‐marginal model. The pattern observed is in agreement with the phenotypic structure across species range. A clear genetic break between populations of Algeria, the Eastern Asia, and the remaining populations is a dominant feature of the data. Differential local adaptations, absence of gene flow between marginal and central populations, and/or incapacity to mate after colonization, have contributed to their distinct genotypic and phenotypic characteristics. Abstract : We provide an empirical test of the central‐marginal model using a widespread species distributed on the entire Palearctic region, focusing on genetic and phenotypic characteristics of the rear‐edge populations. The genetic diversity and differentiation observed is in agreement with the phenotypic structure across species range. A clear genetic break between populations of Algeria, the Eastern Asia and the remaining populations is a dominant feature of the data. We discuss factors, as historical isolation and/or local adaptation, which may have contributed to their distinct genotypic and phenotypic characteristics.